2013
DOI: 10.1103/physrevb.88.075418
|View full text |Cite
|
Sign up to set email alerts
|

Mixing of edge states at a bipolar graphene junction

Abstract: An Atomic Force Microscope is used to locally manipulate a single layer graphene sheet. Transport measurements in this region as well as in the unmanipulated part reveal different charge carrier densities while mobilities stay in the order of 10 4 cm 2 (Vs) −1 . With a global backgate, the system is tuned from a unipolar n-n' or p-p' junction with different densities to a bipolar p-n junction. Magnetotransport across this junction verifies its nature, showing the expected quantized resistance values as well as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
(32 reference statements)
1
30
0
Order By: Relevance
“…In the limit of large temperatures (k B T much larger than the Thouless energy of the interface) the Fano factor becomes 52 F = T (1 − T ) / T , which may be easily evaluated by combining Eqs. (34) and (35). In the limit of a clean junction one then finds the same Fano factor as in the zero temperature limit, whereas in the strong disorder limit L l i , l a the high-temperature limit is…”
Section: Scaling Approach For the Scattering Matrixmentioning
confidence: 96%
See 1 more Smart Citation
“…In the limit of large temperatures (k B T much larger than the Thouless energy of the interface) the Fano factor becomes 52 F = T (1 − T ) / T , which may be easily evaluated by combining Eqs. (34) and (35). In the limit of a clean junction one then finds the same Fano factor as in the zero temperature limit, whereas in the strong disorder limit L l i , l a the high-temperature limit is…”
Section: Scaling Approach For the Scattering Matrixmentioning
confidence: 96%
“…31 Several experimental groups have performed measurements of the two-terminal conductance of graphene pn junctions in a large perpendicular magnetic field. [15][16][17][18][32][33][34][35][36] The measured conductance follows the ensemble average of the strongly disordered limit of Ref. 24, although the experimentally observed mesoscopic fluctuations remain significantly below the theoretical prediction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to conductance measurements, [13][14][15][16][17][18][19][20][21][22][23][24] shot noise measurements 25,26 have demonstrated that a graphene n-p junction can act as a coherent beam splitter of electron-like and hole-like particles. Recently, a Mach-Zehnder edge-channel interferometer has been implemented in such a device, showing robust conductance oscillations with very high visibility.…”
Section: Introductionmentioning
confidence: 99%
“…This can be realized by making a p-n junction in graphene [6][7][8], where the four chiral states propagate along the junction preserving the valley degeneracy. In recent years graphene p-n junction with perpendicular magnetic field has gained a lot of attention in condensed matter physics [9][10][11][12][13][14][15][16][17][18][19]. Such a p-n junction exhibits unprecedented phenomena like snake states [9,12,13], where the interface state in a semi-classical picture alternatively propagate in the p and n side of the junction.…”
Section: Introductionmentioning
confidence: 99%
“…In an experiment, as there will be only one unique disorder configuration and thus, the CFs should emerge. For last one decade several experiments [7,8,10,11,17,[21][22][23][24][25][26][27][28][29][30][31] have been performed on graphene p-n junction devices. Most of the experiments were carried out on SiO 2 substrate as global back gate and Al 2 O 3 / HSQ/ PMMA/ air bridge as a local top gate.…”
Section: Introductionmentioning
confidence: 99%